2015
DOI: 10.1152/ajpheart.00908.2014
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific finite element analysis of ascending aorta aneurysms

Abstract: Martin C, Sun W, Elefteriades J. Patient-specific finite element analysis of ascending aorta aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 41 publications
2
84
0
Order By: Relevance
“…As our community moves forward to more patient-based geometries and simulations involving realistic geometries that necessarily lead to complex stress fields, validation of models in multidimensional loading is crucial. For example, it is common [62][63][64][65][66] to report results in terms of principal stresses, which are informative but do not address the fact that a stress acting radially or in shear is more likely to lead to tissue failure than one acting circumferentially. Martin et al [65] used a potentially generalizable energy-based failure threshold, but they based the failure criterion on uniaxial circumferential tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our community moves forward to more patient-based geometries and simulations involving realistic geometries that necessarily lead to complex stress fields, validation of models in multidimensional loading is crucial. For example, it is common [62][63][64][65][66] to report results in terms of principal stresses, which are informative but do not address the fact that a stress acting radially or in shear is more likely to lead to tissue failure than one acting circumferentially. Martin et al [65] used a potentially generalizable energy-based failure threshold, but they based the failure criterion on uniaxial circumferential tests.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is common [62][63][64][65][66] to report results in terms of principal stresses, which are informative but do not address the fact that a stress acting radially or in shear is more likely to lead to tissue failure than one acting circumferentially. Martin et al [65] used a potentially generalizable energy-based failure threshold, but they based the failure criterion on uniaxial circumferential tests. Although Martin's work represents a significant advance and demonstrates the potential of the patient-specific FE approach, there is clear need for a more accurate failure model, which could be informed by the current work.…”
Section: Discussionmentioning
confidence: 99%
“…Examining surgical specimens, the ‘delamination strength’ of aneurysmal aortic tissue was significantly lower with BAV as compared to TAV 38. However, in a study of aneurysm patients undergoing surgery, there was no correlation found between experimental rupture risk between BAV and TAV aneurysms 39. Currently, in vivo data about the correlation between size of BAV-associated aortic aneurysm, BSA, age, and gender and risk of acute aortic events are very limited.…”
Section: Could Biomechanical Analysis Of the Ascending Aorta Predict mentioning
confidence: 98%
“…Potential factors influencing the risk of aortic dissection in the setting of aortic aneurysm may include gender, body size, family history, aortic growth rate, BAV morphology, aortic dilatation phenotype, aortic wall stress and valve dysfunction 1 32 39…”
Section: Prognostic Factors In Patients With Bav Aortopathymentioning
confidence: 99%
“…Finite element (FE) analyses have been utilized for studying aortic aneurysm biomechanics and rupture risk (Celi and Berti 2014; Doyle et al 2009; Erhart et al 2015; Fillinger et al 2002; Gasser 2016; Georgakarakos et al 2010; Maier et al 2010; Martin et al 2015; Rodríguez et al 2008; Venkatasubramaniam et al 2004; Vorp et al 1998). The main limitations in these studies are the use of simplified and isotropic tissue properties (Celi and Berti 2014; Doyle et al 2009; Fillinger et al 2002; Georgakarakos et al 2010; Maier et al 2010; Vorp et al 1998), idealized geometries (Celi and Berti 2014; Rodríguez et al 2008; Vorp et al 1998), neglect of pre-stress (Celi and Berti 2014; Doyle et al 2009; Georgakarakos et al 2010) and lack of tissue failure criteria (Celi and Berti 2014; Doyle et al 2009; Georgakarakos et al 2010; Rodríguez et al 2008).…”
Section: Introductionmentioning
confidence: 99%